(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The purpose of this article is the phraseological systems of the Uzbek and English languages, studied in a comparative-typological aspect. And also to analyze the semantic and linguocultural features of the phraseological units of the Uzbek and English languages, systemic relations in the phrase systems of these languages, phraseological pictures of the world of the peoples-carriers of the compared languages.